2021
DOI: 10.1111/aphw.12271
|View full text |Cite
|
Sign up to set email alerts
|

Acculturative stress and coping among migrant workers: A global mixed‐methods systematic review

Abstract: No existing review has synthesized key questions about acculturation experiences among international migrant workers. This review aimed to explore (1) What are global migrant workers’ experiences with acculturation and acculturative stress? (2) What are acculturative stress coping strategies used by migrant workers? And (3) how effective are these strategies for migrant workers in assisting their acculturation in the host countries? Peer‐reviewed and gray literature, without time limitation, were searched in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…In particular, migrant workers with local language active skills (i.e., writing and speaking in Cantonese) were less likely to experience clinically meaningful symptoms of anxiety; and they who passively fluent in the local language (i.e., reading and listening in Cantonese) and actively fluent in English (i.e., writing and speaking) were less likely to experience clinically meaningful symptoms of depression compared to migrant workers with poor language fluency. These findings supported previous studies that found a language mastery was a key skill in wellbeing, help-seeking behavior, and successful acculturation process and low acculturative stress by adjusting with new values or norms in the new environment among migrants globally [10][11][12].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In particular, migrant workers with local language active skills (i.e., writing and speaking in Cantonese) were less likely to experience clinically meaningful symptoms of anxiety; and they who passively fluent in the local language (i.e., reading and listening in Cantonese) and actively fluent in English (i.e., writing and speaking) were less likely to experience clinically meaningful symptoms of depression compared to migrant workers with poor language fluency. These findings supported previous studies that found a language mastery was a key skill in wellbeing, help-seeking behavior, and successful acculturation process and low acculturative stress by adjusting with new values or norms in the new environment among migrants globally [10][11][12].…”
Section: Discussionsupporting
confidence: 90%
“…Total score can also be categorized into four levels of severity: none (<5), mild (5)(6)(7)(8)(9), moderate (10)(11)(12)(13)(14), and severe (>14). The Cronbach's alpha of GAD-7 in this study was .91 comparable to the previous study among earthquake survivors in Indonesia (α = .88) [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, OFWs and other migrant workers struggle to fulfill their health needs because of systemic barriers they experience including language difficulties, adverse working conditions, lack of available healthcare providers, and inadequate social protection for migrant workers in the host countries ( 3 , 4 ). Consequently, migrant workers, including OFWs, experience higher risks for developing mental disorders like anxiety and depression than local people in the host countries ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, during the process of acculturation, migrants may face numerous adaptation challenges, which are detrimental to their psychological and physical health (Choy et al, 2020). Liem et al's (2021*) review illuminates the acculturation process of Chinese rural‐to‐urban migrants and highlights the importance of coping strategies during the process.…”
mentioning
confidence: 99%